Evaluating The Effectiveness Of Near-Peer Teaching Modality In Undergraduate Dental Students Learning A Psychomotor Skill (Partial Denture Fabrication) Considering Social And Cognitive Congruence Factors - Irshad, Saima; Orakzai, Gulmina Saeed; Nisa, Waqar-Un; Khan, Nauman Bari; Ali, Misbah; Farooq, Saba (Journal of Rawalpindi Medical College, 2024)
Objective: To analyze the effectiveness of Near Peer Teaching (NPT) modality in the psychomotor skills development of dental students in fabricating removable partial dentures considering cognitive and social congruence factors Methods: This sequential two-phase experimental study was carried out from September 2022- December 2022 at Watim Dental College Rawalpindi. 50 Students of second-year BDS and recently graduated dental interns who were doing House jobs participated in the study. 50 students were divided into 2 groups A and B respectively. Quantitative data was collected against a 5-point performance appraisal rating scale and feedback from students was taken using a course experience questionnaire. The quantitative data was analyzed using SPSS-23. Descriptive statistics and the Whitney U test were applied to make a comparison between tutoring techniques. P-value ≤ 0.05 was considered significant. The qualitative data gathered through three Focus Group Discussions (two tutee groups and one peer tutor group) was analyzed through thematic analysis. Results: All the participants (50) of the survey were in the age group 20-24 years and female students outnumbered the males (7:1). The Mann-Whitney U test applied to make a comparison between experienced and near-peer tutoring modality showed greater student satisfaction with near-peer teaching. Focus group discussion also revealed various themes such as the benefits of experience as NPT, skills achieved and enhanced motivation thus supporting the “Involvement of NPT in dental education”. Conclusion: It can be concluded that the near-peer teaching technique is advantageous and feasible for both tutees and tutors because of social and cognitive factors. Near-peer tutors have more cognitive congruence and are more socially active in helping their peers. Near peer tutors endorse this technique as it allows them to enhance their knowledge and improve their communication and professional skills.